PENGARUH PEMBERIAN RANSUM PABRIK DENGAN PENAMBAHAN DAUN PEPAYA DAN DEDAK PADI TERHADAP PERTUMBUHAN AYAM KAMPUNG SUPER - Sulastri, Sulastri; Hamdani, Asrul; Sudirman, Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Super native chickens are a cross between native chickens and laying hens. Super native chickens require nutritious feed to achieve optimal production results. This study aims to determine the effect of providing factory rations with the addition of papaya leaves and rice bran on the growth of super native chickens. The study was conducted from January 2026 to March 2026 using a completely randomized design with 5 treatments and 4 replications. Data analysis was carried out through analysis of feed consumption, daily body weight gain, feed conversion, and feed efficiency using analysis of variance in a completely randomized design (CRD). The results showed that all research variables, such as feed consumption, daily body weight gain, feed conversion, and feed efficiency, had the highest average values ​​in the P0 treatment with 50% Factory Ration + (100% Papaya Leaves + 0% Rice Bran), with average feed consumption ranging from 85.66-92.71 g/head/day, daily body weight gain of 413.74-471.71 g/head/day, feed conversion of 0.22-0.20 g, and feed efficiency of 455.93% to 508.82%.